Log in to add a comment

## Answers

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

A:B= 4:9

A = 4

But in A:C A=2

therefore,

A:B = (4:9)x1

A:C =(2:3)x2

=4:6

by this we get A = 4

therefore C = 6

therefore A:B:C = 4:9:6

A = 4

But in A:C A=2

therefore,

A:B = (4:9)x1

A:C =(2:3)x2

=4:6

by this we get A = 4

therefore C = 6

therefore A:B:C = 4:9:6

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

__A : B : C = 4 : 9 : 6__

__Because by the given ratio B is 9/4*A and C is 3/2 * A__

__and putting these in A: B : C = 1: 9/4 : 3/2__

__CONVERTING IN SIMPLE RATIO MULTILPY BY 4__